The Implementation of Audio-Lingual Method In Improving Speaking Skill At The Tenth Grade Students of Ma Al-Khairat Bintauna - Nur Yolanda Alamri; Indahyanti, Rizka; Sulviana, Sulviana (AIJER: Algazali International Journal Of Educational Research, 2024)
This study used a quantitative experimental method through 2 classes, namely the experimental class and the control class. The population of this study was students of class X MA Al-Khairat Bintauna. The number of samples in this study consisted of 22 students in class A and 23 students in class B. This study aims to improve students' speaking skills and interest through the Audio-lingual method in class X MA Al-Khairat Bintauna. The population in this study was MA Al-Khairat Bintauna which consisted of 2 classes with 45 students and focused on 22 students in class X A. The instruments used to collect data were speaking tests in the form of conversations and questionnaire. The results of these data indicate that the average pretest score of class X A students in the experiment was 50,91. While the average value of the post-test is 81.09 which is higher than the pre-test. While the average value of students in control class X B is 45.59 And the post test score is lower than the pre test average score of 39,00. This shows that there was no increase in the control class, while in the experimental class there was a significant increase in the results of applying the Audio-Lingual method from pre-test to post-test for the experimental class in improving students' speaking skills with a result of 33,13.